Análise da relação trabalho e saúde de psicólogos dos Núcleos de Apoio à Saúde da Família – NASF - Lucena, Maria do Socorro Roberto de (2017)
Psychologists are officially included in basic care through their role in the Family Health Support Centers (Núcleos de Apoio à Saúde da Família - NASF). Against this backdrop, these professionals start to experience a different and complex work environment, which distances itself considerably from the traditional spaces of action, such as clinics and offices. In this sense, the psychologist is also confronted with working in the scenario of public health, which sometimes occurs under precarious conditions and puts workers in contact with suffering and social problems on a daily basis. Thus, considering this context and understanding that the work can influence positively or negatively the health of these workers, this dissertation has as general objective to analyze the relation between work and health of psychologists at the NASFs. As theoretical approach used in this paper, the Psychodynamics of work was discussed, since it allows to investigate the subject through subjective experiences in a contextual and dynamic way. As for the method, this research is a qualitative study. The instruments used were a sociodemographic questionnaire, and a semi-structured interview script. Observations of the work were also made. The perspective adopted for the analysis of the data was the category content analysis. Seven psychologists aged between 2 9 and 53 years, the majority being female, took part in the survey. The results were organized and presented in four thematic categories: work organization of the supportive psychologist; The activity of the NASF psychologist; Intersubjective relationships: with colleagues, hierarchical supervisors, and users; And work-health-disease process. These categories reveal the reality of the work of these professionals, as well as the health conditions of the workers. In summary, the development of practical intelligence, subjective mobilization, and cooperation are seen as necessary for psychologists to achieve the objectives in their activity. Moreover, it is observed that the relationship of psychologists with the obstacles in their work is sometimes experienced pleasantly, sometimes as a source of suffering, depending on organizational conditions. Thus, we highlight the spaces for inventiveness and autonomy, the intersubjective relations based on solidarity and recognition, as fundamental conditions for not breaking the subjective mobilization and also as ways of promoting health in the activity of these professionals.